Respuesta :
Answer:
equation: y = x² + 2x + 5
Step-by-step explanation:
y = ax² + bx + c
(y = ax^2 + b + c can't have a solution, must be y = ax^2 + bx + c)
passes through the points (1, 8), (0, 5) and (3, 20)
8 = a x 1² + b x 1 + c = a + b + c .......(1)
5 = a x 0² + b x 0 + c = c
20 = a x 3² + b x 3 + c = 9a + 3b + c .......(2)
8 = a + b + 5
a + b = 3 9a + 9b = 27
9a + 3b = 15
6b = 12
b = 2
a = 1
equation: y = x² + 2x + 5
Answer:
Step-by-step explanation:
y=ax²+bx+c
at (1,8)
8=a(1)²+b(1)+c
or
a+b+c=8 ...(1)
at (0,5)
5=a(0)²+b(0)+c
c=5
so a+b+5=8
a+b=8-5=3
a+b=3 ...(2)
at (3,20)
20=a(3)²+b(3)+c
20=9a+3b+5
9a+3b=20-5=15
3a+b=5 ...(3)
subtract (2) from (3)
3a+b-a-b=5-3
2a=2
a=2/2=1
from (2)
1+b=3
b=3-1=2
so y=x²+2x+5